Ursus arctos - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2009)
7. Brown Bear Ursus arctos French: Ours brun / German: Braunbär / Spanish: Oso pardo Other common names: Grizzly Bear, Kodiak Bear Taxonomy. Ursus arctos Linnaeus, 1758, northern Sweden. Genetic data corroborate the distinctiveness of some subspecies, such as isabellinus in Central Asia, but not others. Eight subspecies have been recognized in North America (seven of which are extant), but genetically these group into only three or four discrete clades, none of which match current subspecies designations. Conversely, whereas only one subspecies (artos) has been recognized for Europe, two geographically distinct lineages have been identified. California race californicus (Merriam, 1896) and north-western Africa race crowthert (Schinz, 1844) are extinct. Fourteen extant subspecies currently recognized. Subspecies and Distribution. U. a. arctos Linnaeus, 1758 — Europe and W Russia. U. a. alascensis Merriam, 1896 — most of Alaska (excluding Alaska Peninsula, SE panhandle & Kodiak Island group). U. a. beringianus Middendorff, 1853 — NE Russia (Kamchatka Peninsula & N Kuril Islands northward through the Koryak Autonomous District, and along W coast of the Sea of Okhotsk). U. a. collaris Cuvier, 1824 — Russia (Siberia, from E of the Yenisey River to the Bering Sea, but excluding Kamchatka and more southern parts of the Russian Far East), N Mongolia. U. a. dalli Merriam, 1896 — SE Alaska (N of Alexander Archipelago). U. a. gyas Merriam, 1902 — Alaska peninsula. U. a. horribilis Ord, 1815 —W Canada (Yukon, North-West Territories, British Columbia & Alberta), inland W USA (extirpated from S Wyoming to Mexico). U. a. isabellinus Horsfield, 1826 — N India, Pakistan, Afghanistan, N to Kazakhstan and Mongolia (Gobi Desert). U. a. lasiotus Gray, 1867 — Russia (Southern Kuril Islands, Sakhalin, Ussuri/ Amur river region of the Russian Far East), NE China, North Korea, and Japan (Hokkaido). U. a. middendorffi Merriam, 1896 — Alaska (Kodiak Island & nearby islands). U. a. pruinosus Blyth, 1853 — Tibetan Plateau, ...